[tex]\bf \begin{cases} f(x)=2x-1\\ g(x)=x^2+3x-1 \end{cases} \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ f(x)+g(x)\implies (2x-1)+(x^2+3x-1)\implies 2x+3x-1-1+x^2 \\\\\\ x^2+5x-2 \\\\[-0.35em] ~\dotfill[/tex]
[tex]\bf f(x)-g(x)\implies (2x-1)-(x^2+3x-1)\implies 2x-1-x^2-3x+1 \\\\\\ -x^2-x \\\\[-0.35em] ~\dotfill\\\\ f(x)\cdot g(x)\implies (2x-1)\cdot (x^2+3x-1) \\\\\\ \stackrel{2x(x^2+3x-1)}{2x^3+6x^2-2x}~~+~~\stackrel{-1(x^2+3x-1)}{(-x^2-3x+1)}\implies 2x^3+5x^2-5x+1 \\\\[-0.35em] ~\dotfill\\\\ \cfrac{f(x)}{g(x)}\implies \cfrac{2x-1}{x^2+3x-1}[/tex]
the division doesn't simplify any further.